Pengaruh Angka Harapan Hidup, Pendidikan dan Kesempatan Kerja Terhadap Kemiskinan di Kabupaten/Kota Provinsi Nusa Tenggara Barat Tahun 2018-2022 - Winarni, Galuh Amelia; Harsono, Iwan; Endang Astuti; Himawan Sutanto; Ida Ayu Putri Suprapti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The study aims analyze the Life Expectancy, Education and Employment Opportunities Against Poverty in the district/city of West Nusa Tenggara Province, from 2018 to 2022. The data is obtained from the Central Statistical Authority of West Nusa Tenggara. The type of data used is sekunder data. Analiysis the data used is Panel data regression analysis with Eviews 12 Application. After doing the analysis, The Research has shown that Partially Life Expectancy have a negative and significant effect on poverty in the districts/cities of West Nusa Tenggara Province. Meanwhile, Education have a positive and insignificant effect on poverty in the districts/cities of West Nusa Tenggara Province Then Employment Opportunity have a negative and insignificant effect on poverty in the district/cities of West Nusa Tenggara Province (4) Simultaneously Variable Life Expectancy, Education, Employment Opportunities together have a significant effect on poverty in the districts/cities of West Nusa Tenggara Province